Gone from these woods - Seagraves, Donny Bailey (Delacorte Press, 2009)
Feeling like a monstrous villain in one of his comic books, eleven-year-old Daniel tries to cope with the guilt after accidentally killing his beloved uncle while hunting in the woods of North Georgia.